2022
DOI: 10.3390/mps5020030
|View full text |Cite
|
Sign up to set email alerts
|

How to Clean and Safely Remove HF from Acid Digestion Solutions for Ultra-Trace Analysis: A Microwave-Assisted Vessel-Inside-Vessel Protocol

Abstract: The complete dissolution of silicate-containing materials, often necessary for elemental determination, is generally performed by microwave-assisted digestion involving the forced use of hydrofluoric acid (HF). Although highly efficient in dissolving silicates, this acid exhibits many detrimental effects (e.g., formation of precipitates, corrosiveness to glassware) that make its removal after digestion essential. The displacement of HF is normally achieved by evaporation in open-vessel systems: atmospheric con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…A novel signal-enhancement strategy for LIBS analysis of soil combined 201 APGD and cylindrical (plasma) connement. The LODs of 2,31,21,35,49,67,43,20 and 18 mg kg −1 for Ba, Cu, Eu, La, Lu, Ni, Ti, Y and Yb, respectively, were signicantly better than the values (10,133,102,175,262,356,246,158 and 105 mg kg −1 , respectively) achievable using conventional LIBS. An alternative approach involved 202 addition of 15% KI to soil samples to increase plasma temperature and electron density.…”
Section: Reference Materialsmentioning
confidence: 81%
See 1 more Smart Citation
“…A novel signal-enhancement strategy for LIBS analysis of soil combined 201 APGD and cylindrical (plasma) connement. The LODs of 2,31,21,35,49,67,43,20 and 18 mg kg −1 for Ba, Cu, Eu, La, Lu, Ni, Ti, Y and Yb, respectively, were signicantly better than the values (10,133,102,175,262,356,246,158 and 105 mg kg −1 , respectively) achievable using conventional LIBS. An alternative approach involved 202 addition of 15% KI to soil samples to increase plasma temperature and electron density.…”
Section: Reference Materialsmentioning
confidence: 81%
“…The authors suggested that microscopic cracks in the Teflon, observed with SEM/EDS, allowed penetration of elements below the Teflon surface, and they proposed the incorporation of additional bar-cleaning steps to avoid transfer of adsorbed PTEs to subsequent samples. A protocol designed to remove HF from samples following microwave digestion had 133 the aim of preventing the introduction of impurities frequently observed with open-vessel HF evaporation. The ‘vessel-inside-vessel’ technique involved sample digestion (with HF and HNO 3 ) in a small (5 mL) loosely-capped inner PFA vessel, after which HF was transferred from the inner vessel into the larger (70 mL) outer PTFE sealed vessel by means of two further microwave cycles at 500 W for 10 min.…”
Section: Analysis Of Soils Plants and Related Materialsmentioning
confidence: 99%
“…For each digestion batch, 3 vessels were used for SiC samples and 2 for reference blanks. The adopted strategy initially involved the exploitation of the “Vessel-Inside-Vessel” technique [ 41 , 42 ] to avoid memory effects [ 43 ]; digestion took place in small capped containers of perfluoroalkoxy (PFA, internal volume = 5 mL) placed inside commercial PTFE vessels. The sample (mass approximately equal to 50 mg) was introduced into the PFA vessel together with the mixture of acids, while 5 mL of ultrapure H 2 O was placed outside of it (i.e., inside the PTFE vessel).…”
Section: Methodsmentioning
confidence: 99%